Research hotspots and frontiers of neuromodulation technology in the last decade: a visualization analysis based on the Web of Science database - Liu, Yanpei; Zhang, Qian; Zhang, Haoran; Xiang, Yun; Wang, Hui (Frontiers in Human Neuroscience, 2025)
BackgroundSince the 1990s, neuromodulation technology has experienced rapid advancements, providing new therapeutic approaches for clinical rehabilitation in neurological disorders. The objective of this study is to utilize CiteSpace and VOSviewer to investigate the current research status, key topics, and future trends in the field of neuromodulation technology over the past decade.MethodsRelevant literature in the field of neuromodulation technology published in Web of Science database from January 1, 2014 to June 18, 2024 were retrieved, and imported into CiteSpace and VOSviewer for visualization. VOSviewer was used for counties, institutions, authors and keywords analyses. CiteSpace was used for presentation visualization analysis of co-cited references, keywords clusters and bursts.ResultsThis study encompasses a total of 1,348 relevant publications, with the number of publications showing an increasing trend year by year. The most significant growth was observed between 2020 and 2021. The United States, China and the United Kingdom are the three leading countries with high output in this regard. The top three institutions in terms of the publication volume are Harvard Medical School, the University of Toronto and Stanford University. Keyword co-occurrence and cluster analysis identified that deep brain stimulation, transcranial magnetic stimulation, transcranial direct current stimulation, and focused ultrasound stimulation are the most widely used central nerve stimulation techniques in neuromodulation. The treatment of intractable chronic pain also emerged as a key focus within neuromodulation techniques. The recent keywords bursts included terms such as recovery, movement, nucleus, modeling and plasticity, suggesting that the future research trend will be centered on these areas.ConclusionIn conclusion, neuromodulation technology is garnering increasing attention from researchers and is currently widely used in brain diseases. Future research is expected to delve deeper, particularly into exploring deep brain structure stimulation targets and restoring motor function based on neuroplasticity theory.